2022
DOI: 10.1182/blood.2021012896
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of platelet CLEC-2 decreases GPIbα-mediated integrin αIIbβ3 activation and decreases thrombosis in TTP

Abstract: Microvascular thrombosis in patients with thrombotic thrombocytopenic purpura (TTP) is initiated by GPIba-mediated platelet binding to von Willebrand factor (VWF). Binding of VWF to GPIba causes activation of the platelet surface integrin aIIbb3. However, the mechanism of GPIba-initiated activation of aIIbb3 and its clinical importance for microvascular thrombosis remain elusive. Deletion of platelet C-type lectin-like receptor 2 (CLEC-2) did not prevent VWF binding to platelets but specifically inhibited plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…In contrast, the adhesion of platelets on plaque under flow is abrogated when the GPVI-collagen interaction is blocked by an anti-GPVI antibody, suggesting platelet activation by plaque is almost entirely mediated by GPVI (47,48). More recently, it has been shown that deletion of CLEC-2 (using the PF4-Cre) decreases GPIb-mediated integrin IIb3 activation, which may also contribute to the loss of platelet activation perfused at arterial shear in the GPIb-Cre + mice (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the adhesion of platelets on plaque under flow is abrogated when the GPVI-collagen interaction is blocked by an anti-GPVI antibody, suggesting platelet activation by plaque is almost entirely mediated by GPVI (47,48). More recently, it has been shown that deletion of CLEC-2 (using the PF4-Cre) decreases GPIb-mediated integrin IIb3 activation, which may also contribute to the loss of platelet activation perfused at arterial shear in the GPIb-Cre + mice (49).…”
Section: Discussionmentioning
confidence: 99%
“…contribute to the loss of platelet activation perfused at arterial shear in the GPIb-Cre + mice (49).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thrombotic thrombocytopenic purpura (TTP) is a potentially fatal disorder characterized by systemic microvascular thrombosis (1). Based on its etiology, TTP can be divided into hereditary TTP and acquired TTP, and the latter can be further divided into idiopathic TTP and secondary TTP according to whether the etiology is clear.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent observations in a mouse model of TTP documented that adhesion of platelet GPIbα to VWF caused activation of the platelet fibrinogen receptor, αIIbβ3, allowing fibrinogen binding and initiation of platelet aggregation (Figure 1). 5 Thrombus size was decreased by pre-treatment of mice with aspirin, which blocks the activation of αIIbβ3, or eptifibatide, which blocks binding of fibrinogen to αIIbβ3. 5 Based on these experimental observations, we considered that aspirin may diminish the risk for stroke and other thrombotic events in patients with hTTP and in iTTP during remission.…”
mentioning
confidence: 99%
“…5 Thrombus size was decreased by pre-treatment of mice with aspirin, which blocks the activation of αIIbβ3, or eptifibatide, which blocks binding of fibrinogen to αIIbβ3. 5 Based on these experimental observations, we considered that aspirin may diminish the risk for stroke and other thrombotic events in patients with hTTP and in iTTP during remission.…”
mentioning
confidence: 99%